Optimization of isothermal amplification method for Mycobacterium tuberculosis detection and visualization method for fieldwork - A?el, Esra; Sağcan, Hasan; Ceyhan, İsmail; Durmaz, Rıza (Türkiye Klinikleri, 2020)
Background/aim: Tuberculosis is still one of the most contagious diseases around the world. Key factors of tuberculosis control are rapid diagnostic, efficient treatment, and prevention of contamination by surveillance and monitoring. However, culture is the gold standard method for laboratory diagnosis of tuberculosis; the results are several weeks to obtain. In order to prevent contamination of tuberculosis, diagnosis must be made in short time and treatment should be started as soon as possible. The aim of this study is to optimize the loop-mediated isothermal amplification (LAMP) method, which provides a much faster and more sensitive result than the polymerase chain reaction (PCR) method and allows the replication of target nucleic acid sequences under isothermal conditions without the need for laboratory infrastructure. Materials and methods: Sputum samples were homogenized with 5% trypsin solution in CaCl2 to obtain DNA. DNA was purified using QIAGEN QIAamp DNA mini kit. LAMP primers were design using Primer explorer V5 program according to IS6110 gene of Mycobacterium tuberculosis. NEB Bst 3.0 DNA polymerase kit was used for LAMP reactions. Besides, LAMP reactions were compared with TaqMan based RT-PCR method using NEB’s Taq polymerase kit. Finally, for visualization of LAMP products, lateral flow dipsticks that produced by Milenia Biotec, colorimetric 2X LAMP master mix that produced by NEB and 2% w/v agarose gel electrophoresis methods were used. Results: Optimum amplification temperature for LAMP was found to be 71.4 °C. The detection limit of the method was 102 CFU/mL and sensitivity was determined 100% compared to five different Mycobacterium species. Conclusion: The current study indicated that the LAMP-LFD and colorimetric LAMP protocol optimized with sputum samples can be reliable used as a rapid, sensitive and specific assay in the diagnosis of tuberculosis in the field.
Keywords: Mycobacterium Tuberculosis; Loop-Mediated Isothermal Amplification; Lateral Flow Dipstick; Colorimetric Detection; Point of Care